Onomatopeta: Developing a Japanese Onomatopoeia Learning-Support System Utilizing Native Speakers Cooperation - Yusuf, Mukarramah; Asaga, Chisato; Watanabe, Chiemi (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2008)
We develop Onomatopedia, an example based onomatopoeia online dictionary for learners of the Japanese language[3]; Onomatopedia collects sentences from the Web. To make Onomatopedia reliable and more effective as a self-learning tool, feedback from native speakers about the sentences in Onomatopedia is needed. Moreover, in learning onomatopoeia, pictures and animations are also known as effective materials. Japanese native speakers are the key subject for solving this problem; however, giving feedback or providing pictures will be obligatory or compulsory, and will not motivate them to make a contribution. In this paper we propose Onomatopeta!, a communication tool for gathering Japanese native speakers. Onomatopeta!is a "onopicture"-sharing website. An onopicture is a picture with onomatopoeic words attached on it in cartoon fashion. Native speakers use our tool in order to have fun, and at the same time, onomatopoeia learning material will accumulate on its own. We also provide two games: Oshoot game and Slider Part, with which we generate a mutual link and coordination between Onomatopedia and Onomatopeta! by performing a machine learning algorithm utilizing data input by users.